1997
DOI: 10.3164/jcbn.23.177
|View full text |Cite
|
Sign up to set email alerts
|

Digestion of Stevioside, a Natural Sweetener, by Various Digestive Enzymes.

Abstract: which hydrolyzed it to both steviol and steviol-16,17ƒ¿-epoxide. Steviol-16,17ƒ¿-epoxide was then completely converted back into steviol. These results suggest that steviol might be the only metabolite produced by the intestinal microflora from various animal species and humans.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
76
1
11

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(90 citation statements)
references
References 19 publications
2
76
1
11
Order By: Relevance
“…Although steviol glycosides share a common metabolic fate in both rats and humans (Wingard et al, 1980;Hutapea et al, 1997;Gardana et al, 2003;Koyama et al, 2003a;Geuns et al, 2007;Roberts and Renwick, 2008;Wheeler et al, 2008;Nikiforov et al, 2013;Purkayastha et al, 2014Purkayastha et al, , 2015Purkayastha et al, , 2016, some differences in pharmacokinetics have been noted. As evaluated by JECFA at their sixty-ninth meeting (JECFA, 2009), studies comparing the pharmacokinetics of steviol and steviol glucuronide following oral administration of steviol glycosides demonstrated substantial differences in the concentration of circulating plasma steviol and steviol glucuronide between rats and humans (Roberts and Renwick, 2008;Wheeler et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although steviol glycosides share a common metabolic fate in both rats and humans (Wingard et al, 1980;Hutapea et al, 1997;Gardana et al, 2003;Koyama et al, 2003a;Geuns et al, 2007;Roberts and Renwick, 2008;Wheeler et al, 2008;Nikiforov et al, 2013;Purkayastha et al, 2014Purkayastha et al, , 2015Purkayastha et al, , 2016, some differences in pharmacokinetics have been noted. As evaluated by JECFA at their sixty-ninth meeting (JECFA, 2009), studies comparing the pharmacokinetics of steviol and steviol glucuronide following oral administration of steviol glycosides demonstrated substantial differences in the concentration of circulating plasma steviol and steviol glucuronide between rats and humans (Roberts and Renwick, 2008;Wheeler et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Steviol glycosides pass undigested through the upper gastrointestinal tract to the colon where they are hydrolyzed to steviol by sequential removal of one sugar moiety at a time, prior to absorption of steviol (Wingard et al, 1980;Hutapea et al, 1997;Gardana et al, 2003;Koyama et al, 2003a,b;Geuns et al, 2003Geuns et al, , 2007Renwick and Tarka, 2008;Purkayastha et al, 2015). In rats (Roberts and Renwick, 2008), pigs (Geuns et al, 2003) and humans Wheeler et al, 2008) exposures to the parent steviol glycosides are negligible following oral exposure.…”
Section: Introductionmentioning
confidence: 99%
“…Alternatively, stevioside is degraded by the bacterial flora of the caecum or colon producing free steviol which is further converted into its glucuronide derivative in the liver and excreted from the body through urine (Geuns et al 2007). An in vitro method of digesting steviosides by various digestive enzymes was studied by Hutapea et al (1997) and it was found that none of the enzymes digested the stevioside but the microflora present in the intestinal tract hydrolysed the stevioside to further compounds steviol and steviol-16,17alpha-epoxide. Eventually, steviol-16,17alpha-epoxide was then completely transformed back into steviol and excreted as steviol glucuronide from the body in urine (Chatsudthipong & Muanprasat 2009).…”
Section: Biotransformationmentioning
confidence: 99%
“…The metabolism of stevioside (purity not reported) was studied by using various digestive enzymes or 8 fluids like salivary α-amylase, pancreatic α-amylase, saliva, pepsin, gastric secretion, pancreatin and 9 intestinal brush border membrane enzymes of rodents as well as by the intestinal microflora of various 10 species including humans (Hutapea et al, 1997). None of these enzymes digested stevioside.…”
Section: Efsa Ans Panel Evaluation:mentioning
confidence: 99%